Topological Darkness: Dispersion Topological Darkness at Multiple Wavelengths and Polarization States (Advanced Optical Materials 12/2017). Issue 12 (June 2017) - Song, Haomin; Zhang, Nan; Duan, Jiyuan; Liu, Zhejun; Gao, Jun; Singer, Matthew H.; Ji, Dengxin; Cheney, Alec R.; Zeng, Xie; Chen, Borui; Jiang, Suhua; Gan, Qiaoqiang
Abstract : Complete suppression of reflection from a given flat or patterned surface is extremely difficult due to inherent roughness and fabrication errors. In article number1700166, Qiaoqiang Gan and co‐workers demonstrate a reflectionless thin film system based on topological effects in dispersion space for multi‐wavelengths and both polarization states using directly deposited thin films and random metal nanoparticles.